Analysis of Accounting Information Systems of Cash Receiving and Disbursement At The National Amil Zakat Body Of North Sumatra Province - Sri Sudiarti; Arnida Wahyuni Lubis; Dimas Rizatia Gumelar (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
Cash is the most liquid asset and prone to theft or fraud, so a good cash receipts and disbursement accounting information system is needed so that the company's financial reports can be trusted. . Therefore, every company must develop an accounting information system for cash receipts and disbursements so that the company does not lag behind which will cause losses for the company itself. This study aims to determine the implementation of the cash receipts and disbursement accounting information system at the National Amil Zakat Board of North Sumatra Province and to determine the problems in implementing the cash receipts and disbursement accounting information system. This type of research is descriptive qualitative research. The type of data used in this study is a type of qualitative data, with data collection techniques carried out using documentation and interviews. The results of this study indicate that the application of the cash receipts and disbursement accounting information system carried out at the Amil Zakat Board of North Sumatra Province has been able to support daily operational activities. The problems in implementing the cash receipts and disbursement accounting information system at the National Amil Zakat Agency for North Sumatra Province, namely; Inadequate components of the accounting information system, such as documents related to cash receipts and disbursements, cash receipts and cash disbursement accounting information systems that are not yet fully computerized and there is still a merger of treasurer and finance functions.